Prominent microglial inclusions in transgenic mouse models of α-synucleinopathy that are distinct from neuronal lesions - Tanriöver, Gaye (Acta Neuropathol Commun, 2020)
Alpha-synucleinopathies are a group of progressive neurodegenerative disorders, characterized by intracellular deposits of aggregated α-synuclein (αS). The clinical heterogeneity of these diseases is thought to be attributed to conformers (or strains) of αS but the contribution of inclusions in various cell types is unclear. The aim of the present work was to study αS conformers among different transgenic (TG) mouse models of α-synucleinopathies. To this end, four different TG mouse models were studied (Prnp-h[A53T]αS; Thy1-h[A53T]αS; Thy1-h[A30P]αS; Thy1-mαS) that overexpress human or murine αS and differed in their age-of-symptom onset and subsequent disease progression. Postmortem analysis of end-stage brains revealed robust neuronal αS pathology as evidenced by accumulation of αS serine 129 (p-αS) phosphorylation in the brainstem of all four TG mouse lines. Overall appearance of the pathology was similar and only modest differences were observed among additionally affected brain regions. To study αS conformers in these mice, we used pentameric formyl thiophene acetic acid (pFTAA), a fluorescent dye with amyloid conformation-dependent spectral properties. Unexpectedly, besides the neuronal αS pathology, we also found abundant pFTAA-positive inclusions in microglia of all four TG mouse lines. These microglial inclusions were also positive for Thioflavin S and showed immunoreactivity with antibodies recognizing the N-terminus of αS, but were largely p-αS-negative. In all four lines, spectral pFTAA analysis revealed conformational differences between microglia and neuronal inclusions but not among the different mouse models. Concomitant with neuronal lesions, microglial inclusions were already present at presymptomatic stages and could also be induced by seeded αS aggregation. Although nature and significance of microglial inclusions for human α-synucleinopathies remain to be clarified, the previously overlooked abundance of microglial inclusions in TG mouse models of α-synucleinopathy bears importance for mechanistic and preclinical-translational studies.